Creativity over Time and Space - A Historical Analysis of European Cities - Michel Serafinelli; Guido Tabellini (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Creativity is often highly concentrated in time and space, and across different domains. What explains the formation and decay of clusters of creativity? We match data on notable individuals born in Europe between the XIth and the XIXth century with historical city data. The production and attraction of creative talent is associated with city institutions that protected economic and political freedoms and promoted local autonomy. Instead, indicators of local economic conditions such as city size and real wages, do not predict creative clusters. We also show that famous creatives are spatially concentrated and clustered across disciplines, that their spatial mobility has remained stable over the centuries, and that creative clusters are persistent but less than population.
Keywords: R10; O10; J61; J24; 330; innovation; agglomeration; political institutions; immigration; gravity; human capital